Cultivation possibilities of Salvia aramiensis in the continental and the mediterranean type of climate - Yenikalaycı, Ahmet (Emirates Journal of Food and Agriculture, 2022)
Salvia aramiensis Rech., a perennial species native to the Eastern Mediterranean, is used for medicinal purposes and as herbal tea. The cultivation possibilities, herbage yield, essential oil content and components of S. aramiensis were investigated in two different elevations (Adana 28 m above sea level (asl) and Pozantı 1200 m asl) in the continental and Mediterranean type of climate for 2 years. The measured plant parameters were plant height, herbage, leaf and flower fresh and dry yields, essential oil content and composition. Plant height differences were not significant at both locations and years. The highest herbage yield (7406 kg ha-1 ) was obtained from Adana in the 1st year and the lowest was (2222 kg ha-1 ) obtained in Pozantı in the 2nd year. Essential oil contents varied between 1.5 and 2.9%. The highest leaf essential oil content and yield were obtained from Adana in the 2nd year and the lowest was obtained from Pozantı in the 1st year. The major essential oil found in the leaves and the flowers were α-pinene, 1,8-cineole, β-pinene, borneol, camphor and viridiflorol at both locations. The results of the study showed that S. aramiensis could better adapt and successfully cultivated under plain conditions of the Eastern Mediterranean region